DAMPAK TEKNOLOGI INFORMASI DALAM HASIL BELAJAR KELAS VII IPS TERPADU DI SMP PERTIWI SITEBA KECAMATAN NANGGALO KOTA PADANG - Alsen, Windo Junianpro (STKIP PGRI Sumbar, 2014)
One of the goals of national education is to the intellectual life of the nation in education that include intelligence, skills, attitudes and behavior in accordance with the values of Pancasila is the outlook of the nation of Indonesia. Indonesian education curriculum has undergone several changes. This is done in order to achieve a quality community, and now also has imposed a more active student learning, and provide opportunities for students to think freely is the main asset for any nation, indulge the growing sophistication of life now that the creation of new technologies that can help humans in finding the latest to help find things that are needed, this research was conducted with the aim of observing and analyzing the impact of information technology in learning outcomes Integrated Social Class VII Semester 2013-2014 school year in junior high Earth Siteba Nangggalo District of Padang. The research is a qualitative, informants were taken with Snow-ball technique, the research informants contacted in sequence. Data collection techniques are interviews, observations, field recording, and shooting. Results showed (1) Positive Impact of Information Technology in Integrated Social learning outcomes Class VII semester 2013-2014 school year in junior high Earth Siteba Nanggalo District of Padang, that is very helpful Information Technology students in the learning process to find the information needed and to complete the task that is given by the Integrated Social Studies teacher. (2) Negative Impact of Information Technology in Integrated Social learning outcomes Class VII semester 2013-2014 school year in junior high Earth Siteba Nanggalo District of Padang. That in addition to the positive effect is also no negative impact to students who misuse this information technology is used to play games and online lessons clock time